Effects of government expenditure on economic growth in Kenya - (1990 - 2012) - Abwoga, Timothy (Strathmore University, 2014)
Given the recent fiscal scenario of the Kenyan government, an explanation of this required studying the impact of government expenditure on economic growth. The specific objectives of the study were to: investigate the existence of a long term relationship between the components of government expenditure and economic growth; and examine the effects of components of government expenditure on GOP growth rate. The data used were government expenditure components that included expenditure on government investment, and government consumption. Sources of data were Kenya government documents and international financial publications. The study applied Vector Auto Regression estimation technique using annual time series data for the period 1960 to 2012 to evaluate the impact of government expenditure on economic growth. The Johansen cointegration tests revealed a long-run relationship between GOP growth rate and the selected components of government expenditure. Further, the Granger- Causality test indicated bi-directional causality between GOP growth rate and components of government expenditure. The results of impulse response functions and variance decomposition revealed that government expenditure on investment, and total government expenditure had a positive effect on economic growth while government consumption had mixed effects. The study concludes by giving policy recommendations based on findings and suggests areas such as optimal level of government expenditure for future studies.
A Research Project submitted in partial fulfilment for the Award of Bachelor of Business Science Financial Economics
Keywords: Government expenditure; Economic growth; Kenya